Other town - Rijula Das (2017)
This thesis is divided into two parts: the first part consists of the creative component of this thesis— Other Town— a novel, and the second part consists of the critical exegesis titled, “Private Bodies, Public Desires: Space and the Transgressive Body.” Other Town is the story of Lalee, a commercial sex worker in the red light district of Shonagachhi, in Kolkata, India. When her next door neighbour, Mohamaya, is violently murdered one January night, Lalee is drawn into a series of events that threaten her survival in Shonagachhi. With limited resources and a varied cast of characters, ranging from an erotica writer, a pimp, a printer, and several social workers, policemen and prostitutes, Lalee negotiates the boundaries of freedom.